Solve for r s=(rL-a)/(b-a)

Math
s=rL-ab-a
Rewrite the equation as rL-ab-a=s.
rL-ab-a=s
Multiply both sides of the equation by b-a.
rL-a=s⋅(b-a)
Remove parentheses.
rL-a=s⋅(b-a)
Simplify s⋅(b-a).
Tap for more steps…
Apply the distributive property.
rL-a=sb+s(-a)
Rewrite using the commutative property of multiplication.
rL-a=sb-sa
rL-a=sb-sa
Add a to both sides of the equation.
rL=sb-sa+a
Divide each term by L and simplify.
Tap for more steps…
Divide each term in rL=sb-sa+a by L.
rLL=sbL+-saL+aL
Cancel the common factor of L.
Tap for more steps…
Cancel the common factor.
rLL=sbL+-saL+aL
Divide r by 1.
r=sbL+-saL+aL
r=sbL+-saL+aL
Move the negative in front of the fraction.
r=sbL-saL+aL
r=sbL-saL+aL
Solve for r s=(rL-a)/(b-a)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top